Leadership, psychological climate, and group decision-making performance - Moordiningsih; Faturochman (Universitas Mercu Buana Yogyakarta, 2023)
The psychological climate that occurs in a group becomes an important external factor that influences the success of the group's performance. The dimensions of the group's psychological climate include: (1) the leaders caring; (2) cohesivity; (3) autonomy; and (4) pressure. This study purposes to examine the influence of the group's psychological climate, especially the leader's caring dimension, which can be interpreted as a form of leadership on group performance. This research was conducted with experiments to empirically test the influence of psychological climate on the group decision-making performance. The experimental design used was a post-treatment measurement design with a (2 x 2 x 2 factorial design which consisted of three independent variables with two levels: leadership: (caring vs uncaring),; autonomy:(autonomous vs non-autonomous),; and pressure: (without time pressure vs with time pressure) using random assignment in group division. The results revealed that the interaction effect of group psychological climate had an effect of 10.3% (F = 3.126; p <0.05; ç2 = 0.103) on group decision-making performance. The influence of the leader's climate, which could also mean the process of leadership in the group gave an effect of 36.7% (F = 15.771; p < 0.01; ç2 = 0.367). on group decision-making performance. This indicated that the group performance was determined more by internal factors within the group, which were the psychological climates of the group, than external factors